The Effects of Family Functioning and Psychological Suzhi Between School Climate and Problem Behaviors - Zhang, Ting; Wang, Zhi (Frontiers in Psychology, 2020)
Problem behaviors have always been a hot topic in the field of adolescent research. It is particularly important to study how problem behaviors are developed. Empirical evidence examining problem behaviors has shared the premise that perceived school climate and family functioning play a role in the development of problem behaviors in adolescents. However, it is less clear whether the interaction of perceived school climate and family functioning can predict problem behaviors in adolescents, and which mechanisms within the process it might affect. The present study developed a moderated mediation model to investigate the relationship between perceived school climate, family functioning, psychological suzhi, and problem behaviors in early adolescents. Participants were 1072 Chinese junior high school students who completed the Perceived School Climate Questionnaire, the Strengths and Difficulties questionnaire (SDQ), the Psychological Suzhi Questionnaire for Middle School Students (PSMQ), and the family APGAR scales (FAPGAR). Data were analyzed using IBM SPSS Statistics version 22.0, including descriptive statistics and correlation analysis. The mediating effect and moderating effect was tested by SPSS PROCESS. Results showed that there was a significant negative correlation between perceived school climate and problem behaviors, a partial mediating role of psychological suzhi between perceived school climate and problem behaviors. Moreover, the influence of perceived school climate on psychological suzhi was moderated by family functioning. Indirect effects were significant in participants with high versus low family functioning. There was an interaction between family and school, and psychological suzhi played an important role between environment and adolescent behaviors. This study validates the combined effect of family systems, school systems, and personal systems on problem behaviors, and has certain guiding significance for the prevention and intervention of problem behaviors among adolescents.